Artificial Intelligence and Attestation of Sustainability Reports. How Can Artificial Intelligence Tools be Used for the Assurance Process of Sustainability Reports? - Di Vaio, Assunta; Zaffar, Anum; Balsalobre-Lorente, Daniel (Publishing House of Wroclaw University of Economics and Business, 2024)
[The present book provides a critical reflection on the state and perspectives of the accountancy and auditors profession, addresses the AI technology's supportive role in accounting and auditing tasks, reporting processes and reports' attestation, as well as stresses the necessity to modify educational curriculums in business accounting in response to changing circumstances, and set the regulatory frameworks regarding the use of generative AI by academics and students. The considerations covered in the book are timely and can be helpful for business practitioners, academics and students. Moreover, the international context of the publication, reference to the latest literature on AI applications in business accounting, and presented research study can make this work valuable for all those interested in the opportunities and threats that AI may bring into the professional lives of many.] z zapowiedzi wydawniczej.
Di Vaio, A., Zaffar, A., and Balsalobre-Lorente, D. (2024). Artificial Intelligence and Attestation of Sustainability Reports. How Can Artificial Intelligence Tools be Used for the Assurance Process of Sustainability Reports? In J. Dyczkowska (Ed.), Human versus Machine: Accounting, Auditing and Education in the Era of Artificial Intelligence (pp. 65-81). Publishing House of Wroclaw University of Economics and Business.